2015
DOI: 10.1007/s10585-015-9736-z
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of lung metastases by the CD26/DPP4 inhibitor Vildagliptin in mice

Abstract: Metastases rather than primary cancers determine nowadays the survival of patients. One of the most common primary malignancies is colorectal cancer and this type of tumor is characterized by a high tendency to spread metastases to the lung and liver. CD26/DPP4 is a transmembrane molecule with enzymatic functions which cleaves biologically active peptides. Recently, CD26/DPP4 has become the focus of cancer research and it was shown that CD26/DPP4-positive cancer cells display increased metastatic activity. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Our results show that DPP4 knockdown cells have lower proliferative activity and enter G0/G1 phase more readily. This finding is in concordance with those observed by Jang et al They showed in their results that after inhibiting DPP4 using vildagliptin, the proliferation of tumor cell was suppressed and the mitotic activity was halted [24]. It is likely that DPP4 regulate the tumor cell growth through generation of chemokines and cytokines, such as IL-6R [7].…”
Section: Discussionsupporting
confidence: 89%
“…Our results show that DPP4 knockdown cells have lower proliferative activity and enter G0/G1 phase more readily. This finding is in concordance with those observed by Jang et al They showed in their results that after inhibiting DPP4 using vildagliptin, the proliferation of tumor cell was suppressed and the mitotic activity was halted [24]. It is likely that DPP4 regulate the tumor cell growth through generation of chemokines and cytokines, such as IL-6R [7].…”
Section: Discussionsupporting
confidence: 89%
“…DPP‐IV inhibition has also drawn significant attention in the field of cancer treatment or diagnosis because DPP‐IV regulates various biological mechanisms and it has been suggested that it can act either promoting or inhibiting tumor progression depending on cancer cell type and tumor microenvironment . For instance, it has been argued whether DPP‐IV must be or must not be administered to cancer patients with diabetes, whereas other studies support the oral administration of DPP‐IV inhibitors in order to either enhance tumor immunotherapy or to slow the growth of different tumors or to suppress colorectal cancer lung metastases in mice . Other studies have demonstrated their therapeutic effects on obesity, neuropathy, and hepatic and renal pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…16 For instance, it has been argued whether DPP-IV must be or must not be administered to cancer patients with diabetes, [17][18][19] whereas other studies support the oral administration of DPP-IV inhibitors in order to either enhance tumor immunotherapy 20 or to slow the growth of different tumors 21-23 or to suppress colorectal cancer lung metastases in mice. 24 Other studies have demonstrated their therapeutic effects on obesity, 25-29 neuropathy, 30 and hepatic 31-37 and renal 38-44 pathologies. Recent studies have also shown that it is possible to design DPP-IV inhibitors with dual bioactivity on other targets involved in cardiovascular diseases like ACE 45 or -adrenergic receptors.…”
mentioning
confidence: 99%
“…CSF2 is one of the pivotal orchestrators of basal breast cancer growth and metastasis [47]. DPP4 shows positive metastatic activity in cancer cells [48]. FN1 plays a critical role in metastasis and is associated with advanced stages and higher metastatic potential in patients with renal cancer [4951].…”
Section: Resultsmentioning
confidence: 99%